Pengaruh Pendidikan Aqidah Terhadap Akhlak Siswa Di SMP Muhammadiyah 1 Surakarta Tahun Pelajaran 2016/2017 - Suliani, Tafina; , Drs. M. Darojat Ariyanto, M.Ag (2017)
Education 'aqidah given at school is not the only decisive factor in the formation of morality of students. However, if the student has a strong faith foundation, then he will not be affected by the bad things brought by internal and external factors. At SMP Muhammadiyah 1 Surakarta where there is education 'aqidah, students are equipped with a very important foundation of faith. From education 'aqidah that has been obtained in school, can be realized in everyday behavior. The formulation of this research problem is how the implementation of aqidah and akhlaq education in SMP Muhammadiyah 1 Surakarta and what is the influence of education 'aqidah towards akhlaq students in SMP Muhammadiyah 1 Surakarta. The object of research is the 7th grade students at SMP Muhammadiyah 1 Surakarta, with the type of field research through quantitative approach. Methods of data collection using questionnaires, interviews, observation, and documentation. And the purpose of this research is to describe the implementation of education 'aqidah and akhlaq in SMP Muhammadiyah 1 Surakarta and to know the influence of education' aqidah to akhlaq students. The results of the study of education 'aqidah and akhlaq in SMP Muhammadiyah 1 Surakarta conducted every 1 hour lessons per week, each subject is taught by 1 teacher. Each teacher's initial review reviewed the material last week. After that the teacher delivered the material, sometimes the teacher asked the students to work on the problems in the book. At the end of the learning the teacher gives motivation to the students. SMP Muhammadiyah 1 Surakarta applies KKM for 77, and so far the average student can reach it. And result from calculation of influence of education 'aqidah to akhlaq got coefficient of correlation influence of free variable of aqidah education (X) to morals student (Y) is equal to 0,52. While for tcount is 3.76. And there is also a significant effect of 'aqidah' education on morality in SMP Muhammadiyah 1 Surakarta in 2017. This is proven by hypothesis testing using simple data analysis with t test obtained tcount larger than ttable, good for 5% (3.76 <0.312 ) And 1% (3.76 <0.403).